2015
DOI: 10.1007/s11947-015-1539-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Frozen Storage and Pasteurization Effects on Strawberry Polyphenols Content

Abstract: The profile of the strawberry polyphenols was analysed on fresh strawberry, immediately after freezing or after pasteurization and during frozen storage of strawberry at −20°C for 360 days. Freezing increased the extractability of (−)-epigallocatechin gallate (60 %), (−)-epicatechin (48 %) and ellagic acid (51 %) and decreased the pelargonidin-3-glucoside (18 %). Direct pasteurization of fresh strawberry increased the extractability for (−)-epigallocatechin gallate (73 %), (−)-epicatechin (45 %) and ellagic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…An increase in catechin (42%) was also observed in strawberry pulp treated at 70 °C for 2 min [ 44 ]. In the same direction, Oliveira et al [ 31 , 32 ] reported increments on (+)-catechin, (–)-epigallocatechin, (–)-epicatechin, and (–)-epigallocatechin gallate levels in entire strawberries pasteurized at 90 °C for 5 min. However, after 360 days of storage at –20 °C and 90 days at 23 °C, the concentration of the monomers decreased compared to the content evaluated immediately after processing, although they were still higher than the fresh control [ 31 , 32 ].…”
Section: Effects Of Processing and Storage Conditions On The Stability Of Polyphenolsmentioning
confidence: 81%
See 1 more Smart Citation
“…An increase in catechin (42%) was also observed in strawberry pulp treated at 70 °C for 2 min [ 44 ]. In the same direction, Oliveira et al [ 31 , 32 ] reported increments on (+)-catechin, (–)-epigallocatechin, (–)-epicatechin, and (–)-epigallocatechin gallate levels in entire strawberries pasteurized at 90 °C for 5 min. However, after 360 days of storage at –20 °C and 90 days at 23 °C, the concentration of the monomers decreased compared to the content evaluated immediately after processing, although they were still higher than the fresh control [ 31 , 32 ].…”
Section: Effects Of Processing and Storage Conditions On The Stability Of Polyphenolsmentioning
confidence: 81%
“…In the same direction, Oliveira et al [ 31 , 32 ] reported increments on (+)-catechin, (–)-epigallocatechin, (–)-epicatechin, and (–)-epigallocatechin gallate levels in entire strawberries pasteurized at 90 °C for 5 min. However, after 360 days of storage at –20 °C and 90 days at 23 °C, the concentration of the monomers decreased compared to the content evaluated immediately after processing, although they were still higher than the fresh control [ 31 , 32 ]. Conversely, a general increase in polymeric PACs was observed in thermally treated (90 °C/2 min) cloudy strawberry juice kept at 4 and 20 °C for six months [ 37 ].…”
Section: Effects Of Processing and Storage Conditions On The Stability Of Polyphenolsmentioning
confidence: 81%
“…Although there are a few studies in the literature investigating the chemical changes that are induced to strawberry polyphenols during freezing (Oliveira et al ., ; Bulut et al ., ), as far as it is known, no previous study examined the effect of freezing process on the bioaccessbility of strawberry polyphenols. Considering that, the aim of this study was (i) to investigate the digestive stability of polyphenols from fresh and frozen strawberries as well as the changes in their antioxidant activity using the standardised in vitro model that simulates oral, gastric and small intestinal digestion, and (ii) to compare effects induced by IQF and CF.…”
Section: Introductionmentioning
confidence: 98%
“…Mostly, according to several studies, the inhibition of polyphenol oxidases and acid hydrolysis could occur; as a result, the TPC increases, and consequently, the AA also increases [18,30,31]. The differences found in TPC and AA when citric acid (C 6 H 8 O 7 ) or lactic acid (C 3 H 6 O 3 ) were used could be explained by its chemical structure and its pH solution, 2.55 and 2.98, respectively.…”
Section: Total Phenolic Compounds and Antioxidant Capacitymentioning
confidence: 99%